203k views
3 votes
Given the following functions f(x) and g(x), solve f over g(−4) and select the correct answer below:

f(x) = 4x − 4

g(x) = x − 1

User Knuton
by
5.4k points

1 Answer

4 votes
x = -4
As g(x) is replaced by g(-4)
plug in -4 for x inside the equation.
g(-4) = (-4) - 1g(-4) = -5
Plug in -4 for x in f(x)f(-4) = 4(-4) - 4f(-4) = -16 - 4f(-4) = -20
Now solve for f(x) over g(x)
remember, f(x) = -20, and g(x) = -5
-20/-5 = 4
4 should be your answer
hope this helpsClick to let others know, how helpful is it

User Falukky
by
5.1k points